2007
DOI: 10.1007/s11606-007-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Are Good Intentions Good Enough?: Informed Consent Without Trained Interpreters

Abstract: OBJECTIVE:To examine the informed consent process when trained language interpreters are unavailable.BACKGROUND: Ensuring sufficient patient understanding for informed consent is especially challenging for patients with Limited English Proficiency (LEP). While US law requires provision of competent translation for LEP patients, such services are commonly unavailable. DESIGN AND PARTICIPANTS:Qualitative data was collected in 8 prenatal genetics clinics in Texas, including interviews and observations with 16 cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(44 citation statements)
references
References 43 publications
(42 reference statements)
1
42
0
1
Order By: Relevance
“…The direct relationship between receipt of PMI services and obtaining defect‐free AIS care may have several explanations. AIS patients who received PMI services may have had an increased understanding of their diagnoses and could have asked clarifying questions to make informed decisions about topics pertaining to issues such as their stroke treatment options and rehabilitation needs 12, 13. Clinicians who engaged PMI services may have leveraged the interpreters’ role as “cultural brokers” to better understand patients’ needs and perspectives and to have more meaningful conversations on topics such as stroke risk reduction and smoking cessation 14, 15, 16.…”
Section: Discussionmentioning
confidence: 99%
“…The direct relationship between receipt of PMI services and obtaining defect‐free AIS care may have several explanations. AIS patients who received PMI services may have had an increased understanding of their diagnoses and could have asked clarifying questions to make informed decisions about topics pertaining to issues such as their stroke treatment options and rehabilitation needs 12, 13. Clinicians who engaged PMI services may have leveraged the interpreters’ role as “cultural brokers” to better understand patients’ needs and perspectives and to have more meaningful conversations on topics such as stroke risk reduction and smoking cessation 14, 15, 16.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 While federal guidelines mandate the use of qualified interpreters for patients with LEP, 19 this is an unfunded mandate, and multiple studies have demonstrated low rates of professional interpreter utilization during hospital encounters, including during informed consent discussions. [20][21][22][23][24][25][26] Time constraints and lack of immediate availability have been implicated by clinicians as major barriers to use of professional interpreters in the hospital. 27 A recent study demonstrated that surgeons' decisions to use professional interpreters for informed consent discussions depended in large part on the rapid availability of interpreter services.…”
mentioning
confidence: 99%
“…37 In writing these guidelines, we have made an attempt to address not only current clinical issues but also those that may arise in the near future. 38 For example, the use of microarray testing in place of conventional karyotyping for fetal chromosomal analysis is increasing the potential for unexpected findings.…”
Section: Psychosocial Issuesmentioning
confidence: 99%